Practice of physical activity and dysmobility syndrome in community-dwelling older adults - dos Santos, Vanessa Ribeiro [UNESP]; Diniz, Tiego Aparecido; Batista, Vitor Cabrera [UNESP]; Júnior, Ismael Forte Freitas [UNESP]; Gobbo, Luís Alberto [UNESP] (Korean Society of Exercise Rehabilitation, 2019)
The aim this study was to analyze the association between insufficient physical activity and dysmobility syndrome (DS) in community-dwelling older adults. In total, 375 subjects were evaluated aged ≥ 60 years. For the diagnosis of DS the presence of ≥ 3 clinical factors was considered: (a) low muscle mass; (b) low muscular strength; (c) low gait speed; (d) high body fat, and (e) osteoporosis. Information relating to the practice of habitual physical activity (HPA) was obtained using a questionnaire and accelerometry. The chi-square test was used to verify the association between HPA and DS and analysis of binary logistic regression to build multiple models. Insufficiently active older adults are approximately 2 times (95% confidence interval, 1.14-3.79) more likely to have DS, independent of body mass index, smoking and ethnicity. The insufficient practice of physical activity is associated with DS in older adults, mainly in women and older.
Keywords: Accelerometry; Body composition; Exercise; Musculoskeletal disease